Promoting strategic agricultural public spending in Nigeria - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
In 2015, the World Bank awarded Nigeria a $100 million grant for the implementation of Nigeria’s public expenditure action plan to reform the country’s agricultural sector. The Nigerian Federal Ministry of Finance drew heavily from IFPRI’s research during its dialogue with the World Bank, which helped Nigeria acquire the grant.